2008
DOI: 10.20450/mjcce.2008.233
|View full text |Cite
|
Sign up to set email alerts
|

Use of zirconium phosphate system as a photocatalyst: Photobleaching of tolonium chloride

Abstract: Water pollution due to effluents from dyes and printing industries poses a serious problem for aquatic life. Photocatalysis has attracted the attention of chemists all over the world because it is an efficient and ecofriendly process to combat the problem of water pollution. Photocatalytic bleaching of tolonium chloride on zirconium phosphate was carried out in presence of light. The progress of the reaction was monitored spectrophotometrically, and it follows pseudo first order kinetics. The effect of variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The photocatalytic activity of Bi 2 O 3 for the treatment of phenolic wastes have been studied by Reddy et al, 16 . Panwar et al, 17 observed the degradation of some dyes using zirconium phosphate photocatalyst. Kothari et al, 18 worked on the photoreduction of Congo red by ascorbic acid and EDTA over cadmium sulphide as photocatalyst.…”
Section: Research Articlementioning
confidence: 99%
“…The photocatalytic activity of Bi 2 O 3 for the treatment of phenolic wastes have been studied by Reddy et al, 16 . Panwar et al, 17 observed the degradation of some dyes using zirconium phosphate photocatalyst. Kothari et al, 18 worked on the photoreduction of Congo red by ascorbic acid and EDTA over cadmium sulphide as photocatalyst.…”
Section: Research Articlementioning
confidence: 99%
“…12 Several researches reported the rate of the photocatalytic reaction in aqueous media strongly depends upon the pH of the suspension. 11,[13][14][15] It was found that the rate of the photocatalytic oxidation of Naphthol Blue Black dye on WO 3 in alkaline aqueous solution is much slower than that in acidic solution. 13 There are some reports show increasing the pH accelerates the photoreduction process 10,11 and acetone formation.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, there are scant publications concerning the use of ZrP for the entrapment of dyes from wastewater or other sources. [6][7][8][9] Two methodologies were applied in this field: (1) the use of ZrP as a photocatalyst support in the photocatalytic degradation of dyes and 6 (2) sorption and/or intercalation of dyes in a-type ZrP. [7][8][9] In the few instances found, a-ZrP revealed to be very efficient in decolorizing dye-containing colored water solutions.…”
Section: Introductionmentioning
confidence: 99%